CAN WE TRANSFORM ASIAN SWAMP BUFFALOES TO IMPORTANT PRODUCERS OF MILK AND MEAT? - Cruz, Libertado C. (Proceeding Buffalo International Conference, 2013)
There are 32.75M swamp buffaloes, mostly found in Asia which represent 20.51% of the worlds buffalo population (FAO, 2012). The history of swamp buffalo is basically a history of small-hold land-based agriculture. For centuries, swamp buffaloes have played a major role in draft animal-dependent farming systems, mainly in the production of major agricultural crops. In recent years, however, developments in land-based agriculture in East and Southeast Asia, such as expansion of irrigation facilities and farm mechanization, have significantly reduced the use of buffaloes as draft animals. Utilization of the existing huge population of swamp buffaloes by crossbreeding and at least 2 generations of backcrossing with dairy breed, and harnessing the age-tested abilities of the small-hold farmers to rear these animals can provide opportunities to earn additional income, and also to meet the growing domestic demand for milk and meat. The technical aspect of such crossbreeding has been a subject of research interest for several years in view of the known differences in their chromosome numbers, swamp buffalo has 2n=48 while the riverine type has 2n=50. Today, there are enough evidences that this effort is feasible. For wide-scale crossbreeding and backcrossing program to succeed, the mechanism needed for its implementation, such as artificial insemination system, has to be institutionalized, primarily because the length of the required period is at least 15 years to achieve results of 3 to 4 generations of backcrossing. In the final analysis, the results of this genetic transformation of swamp buffaloes will find more meaning if the